Livestock sector development—Jimmy Smith interview at IFAH-Europe 2015 Conference - Smith, Jimmy W. (International Livestock Research Institute, 2015)
Jimmy Smith, director general of ILRI, speaks about opportunities for livestock sector development on the sidelines of the 2015 International Federation for Animal Health (IFAH)-Europe conference in Brussels, June 2015. Produced by Nik Wood Communications.